2020
DOI: 10.1093/intqhc/mzaa144
|View full text |Cite
|
Sign up to set email alerts
|

Thirty-day readmission rate of COVID-19 patients discharged from a tertiary care university hospital in Turkey: an observational, single-center study

Abstract: Background The 30-day readmission rate is an important indicator of patient safety and hospital’s quality performance. In this study, we aimed to find out the 30-day readmission rate of mild and moderate severity COVID-19 patients discharged from a tertiary care university hospital and to demonstrate the possible factors associated with readmission. Methods This is an observational, single-center study. Epidemiological and cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
60
6
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(69 citation statements)
references
References 29 publications
2
60
6
1
Order By: Relevance
“…Previous studies of outcomes following COVID-19 have focused mainly on survival during hospitalization, and the few studies that have linked discharged patient to longer-term outcomes have been too small to assess differences by demographic factors 3 , 4 ; neither have such studies tended to consider the importance of death as a competing risk when analyzing readmissions post-discharge. 7–9 A recent study in Michigan State (USA) found a high rate of major adverse events following admission for COVID-19, with one-fifth (22%) of patients readmitted or dead within 60 days, 10 but risk factors for such outcomes were not assessed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies of outcomes following COVID-19 have focused mainly on survival during hospitalization, and the few studies that have linked discharged patient to longer-term outcomes have been too small to assess differences by demographic factors 3 , 4 ; neither have such studies tended to consider the importance of death as a competing risk when analyzing readmissions post-discharge. 7–9 A recent study in Michigan State (USA) found a high rate of major adverse events following admission for COVID-19, with one-fifth (22%) of patients readmitted or dead within 60 days, 10 but risk factors for such outcomes were not assessed.…”
Section: Discussionmentioning
confidence: 99%
“…In particular, there is limited information on risk factors for adverse outcomes following discharge, such as readmission or death; previous studies have tended to be too small to assess variation by patient characteristics. 3 , 4 This study describes the variation in the risk of readmission or death within 60 days of discharge following hospitalization for COVID-19, by age, sex and ethnicity.…”
Section: Introductionmentioning
confidence: 99%
“…In the follow-up of 279 discharged patients in Rhode Island of the United States, 30 days after discharge, readmission rate was reported 6.7% (11). In a study done in Turkish study, 7.1% of discharged patients were readmitted (15). The readmission rate of 106,543 COVID-19 patients discharged from the hospital two months after discharge was 9% in the United States (9).…”
Section: Discussionmentioning
confidence: 99%
“…Mostly male gender, old age and the presence of underlying disease or history of malignancy are associated with poor prognosis and readmission in this group of patients (11,12,15). Paying too much attention to COVID-19 pandemic has caused deception to pay attention to other serious diseases such as neoplasms or cardiovascular diseases, which leads to increased mortality in populations and based on the experience of previous respiratory pandemics, the effective use of hospital beds should be an essential goal in the pandemic (4,(16)(17)(18).…”
Section: Introductionmentioning
confidence: 97%
“…Our 30-day hospital readmission rate of 11% is higher than most reported comparisons both in the US (2.2% overall readmission rate in New York City [ 6 ], 6.8% 30-day hospital readmission in Rhode Island [ 7 ], 10.3% overall hospital readmission in Boston [ 8 ]) and globally (2.3% overall hospital readmission in Wuhan [ 9 ], 4.4% overall hospital readmission in Madrid [ 10 ], 4.5% overall hospital readmission in South Korea [ 11 ], 7.1% 30-day hospital readmission in Turkey [ 12 ]). This could reflect the fact that some studies defined readmissions more strictly as COVID-related presentation or that some were confounded by a large number of patients remaining hospitalized during the study time period.…”
mentioning
confidence: 99%